2002
DOI: 10.1016/s0042-6989(02)00018-4
|View full text |Cite
|
Sign up to set email alerts
|

Directional performance in motion transparency

Abstract: Motion transparency provides a challenging test case for our understanding of how visual motion, and other attributes, are computed and represented in the brain. However, previous studies of visual transparency have used subjective criteria which do not confirm the existence of independent representations of the superimposed motions. We have developed measures of performance in motion transparency that require observers to extract information about two motions jointly, and therefore test the information that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
100
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 82 publications
(117 citation statements)
references
References 19 publications
15
100
1
Order By: Relevance
“…3) (Marshak and Sekuler, 1979;Braddick et al, 2002). Direction repulsion has also been observed for transparent stimuli (Braddick et al, 2002;Benton and Curran, 2003;Treue et al, 2000), and it has been suggested that it originates from global mechanisms rather than local ones (Benton and Curran, 2003), which is in agreement with our work. In global Fourier space, transparent stimuli share a lot of properties with non-transparent stimuli, and could be treated using the proposed framework by allowing more than one motion to be computed for each point.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…3) (Marshak and Sekuler, 1979;Braddick et al, 2002). Direction repulsion has also been observed for transparent stimuli (Braddick et al, 2002;Benton and Curran, 2003;Treue et al, 2000), and it has been suggested that it originates from global mechanisms rather than local ones (Benton and Curran, 2003), which is in agreement with our work. In global Fourier space, transparent stimuli share a lot of properties with non-transparent stimuli, and could be treated using the proposed framework by allowing more than one motion to be computed for each point.…”
Section: Discussionsupporting
confidence: 92%
“…This decrease matches the perceptually measured decay of the motion-repulsion effect for large angles (see Fig. 3) (Marshak and Sekuler, 1979;Braddick et al, 2002). Direction repulsion has also been observed for transparent stimuli (Braddick et al, 2002;Benton and Curran, 2003;Treue et al, 2000), and it has been suggested that it originates from global mechanisms rather than local ones (Benton and Curran, 2003), which is in agreement with our work.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations